(3JJeI GdEHGfI aj Ydhe GdOjGfI dCHi GdbGSe GdahQGfi GdeQhRis - (3YHO GdQMef Hf eCehf GdfjSGHhQqi, CHh SYO, GdeYQha HGdoenJnhpqdj , (B478 (3g` s; (3YHO GdQMef Hf eMeO Hf CMeO Hf ahQGf, CHh GdbGSe,J (B461 (3g` s
(3ChdgG (B:s
(3jHJOi HcJGH GdNdY s
(3BNQgG (B:s
(3hjfJgi BNQ cJGH GddYGf s
(3ef GdfSNI faSgGs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B169s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B294 s
Keywords: (3Gdabg GdTGaYjs